Development and implementation of a standardised emergency department intershift handover tool to improve physician communication. Issue 1 (3rd February 2020) - Kwok, Edmund S H; Clapham, Glenda; White, Shannon; Austin, Michael; Calder, Lisa A
Abstract : Background: Structured handover can reduce communication breakdowns and potential medical errors. In our emergency department (ED) we identified a safety risk due to variation in quality and content of overnight handovers between physicians. Aim: Our goal was to develop and implement a standardised ED-specific handover tool using quality improvement (QI) methodology. We aimed to increase the proportion of patients having adequate handover information conveyed at overnight shift change from a baseline of 50%–75% in 4 months. Methods: We used published best practices, stakeholder input and local data to develop a tool customised for intershift ED handovers. Implementation methods included education, cognitive aids, policy change and plan-do-study-act cycles informed by end-user feedback. We monitored progress using direct observation convenience sampling. Measures: Our outcome measure was proportion of adequate patient handovers (defined as >50% of handover components communicated per patient) per overnight handover session. Tool utilisation characteristics were used for process measurement, and time metrics for balancing measures. We report changes using statistical process control charts and descriptive statistics. Results: We observed 49 overnight handover sessions from 2017 to 2019, evaluating handovers of 850 patients. Our improvement target was met in 10 months (median=76.1%) and proportion of adequate handovers continued to improve to median=83.0% at the postimprovement audit. Written communication of handover information increased from a median of 19.2% to 68.7%. Handover time increased by median=31 s per patient. End-users subjectively reported improved communication quality and value for resident education. Conclusions: We achieved sustained improvements in the amount of information communicated during physician ED handovers using established QI methodologies. Engaging stakeholders in handover tool customisation for local context was an important success factor. We believe this approach can be easily adopted by any ED.